Reduced haemodynamic coupling and exercise are associated with vascular stiffening in pulmonary arterial hypertension. Issue 6 (26th August 2016) - Bellofiore, Alessandro; Dinges, Eric; Naeije, Robert; Mkrdichian, Hamorabi; Beussink-Nelson, Lauren; Bailey, Melissa; Cuttica, Michael J; Sweis, Ranya; Runo, James R; Keevil, Jon G; Francois, Christopher J; Shah, Sanjiv J; et al.
Abstract : Objective: Inadequate right ventricular (RV) and pulmonary arterial (PA) functional responses to exercise are important yet poorly understood features of pulmonary arterial hypertension (PAH). This study combined invasive catheterisation with echocardiography to assess RV afterload, RV function and ventricular–vascular coupling in subjects with PAH. Methods: Twenty-six subjects with PAH were prospectively recruited to undergo right heart catheterisation and Doppler echocardiography at rest and during incremental exercise, and cardiac MRI at rest. Measurements at rest included basic haemodynamics, RV function and coupling efficiency (η). Measurements during incremental exercise included pulmonary vascular resistance (Z0 ), characteristic impedance (ZC, a measure of proximal PA stiffness) and proximal and distal PA compliance (CPA ). Results: In patients with PAH, the proximal PAs were significantly stiffer at maximum exercise (ZC =2.31±0.38 vs 1.33±0.15 WU×m 2 at rest; p=0.003) and PA compliance was decreased (CPA =0.88±0.10 vs 1.32±0.17 mL/mm Hg/m 2 at rest; p=0.0002). Z0 did not change with exercise. As a result, the resistance–compliance (RC) time decreased with exercise (0.67±0.05 vs 1.00±0.07 s at rest; p<10 −6 ). When patients were grouped according to resting coupling efficiency, those with poorer η exhibited stiffer proximal PAs at rest, a lower maximum exercise level, and more limited CPA reduction at maximum exercise. Conclusions: In PAH, exercise causes proximal and distal PA stiffening, which combined with preserved Z0 results in decreased RC time with exercise. Stiff PAs at rest may also contribute to poor haemodynamic coupling, reflecting reduced pulmonary vascular reserve that contributes to limit the maximum exercise level tolerated.